Adaptation of the Maternal and Paternal Antenatal Attachment Scale (Condon, 1993): A study with Portuguese couples - Camarneiro, Ana Paula Forte (2010)
Adaptation of the Maternal and Paternal Antenatal Attachment Scale (Condon, 1993): A study with Portuguese couples